Estudo das eletrodeposições de lítio e gálio sobre Au(111) e HOPG utilizando líquido iônico como eletrólito - Gasparotto, Luiz Henrique da Silva (Universidade Federal de São Carlos, 2009)
In the present work, the electrodepositions of lithium and gallium on Au(111) and HOPG (highly oriented phyrolytic graphite) were studied using ionic liquids (ILs) as electrolytes and employing the following techniques: cyclic voltammetry, chronoamperometry, scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), secondary ion-mass spectrometry (SIMS), and in situ scanning tunnelling microscopy (in situ STM). Initially, it was found that the residual water drastically decreases the electrochemical window of the ILs 1-butyl-3- methylimidazolium tetrafluoroborate [(BMIm)BF4] and 1-butyl-3-methylimidazolium hexafluorophosphate [(BMIm)PF6]. Then, in situ STM measurements showed that the organic cation plays a fundamental role on the behaviour of Au(111) in the pure ILs 1-butyl-3-methylpyrrolidinium bis trifluoromethylsulfonil)imide [(BMP)Tf2N] and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonil)imide [(EMIm)Tf2N]. The cyclic voltammograms for gallium deposition on Au(111) suggested that the Au-Ga alloy formation precedes the bulk gallium deposition and in situ STM images revealed a thin gallium layer on Au(111) at the open circuit potential. The thickness of the gallium film potentiostically obtained was 40 nm, at least. Gallium nucleation on HOPG did not follow any of the applied nucleation mechanism (instantaneous or progressive) and, for short-time potential pulses, gallium spheres were formed predominantly along the HOPG step edges. The voltammogram for the lithium deposition on Au(111) revealed an UPD process, solid electrolyte interface formation, lithium bulk deposition and its oxidation. The SEM micrographs showed that the lithium electrodeposit is composed by polygonal crystals and the SIMS analysis confirmed that the deposit was metallic lithium. The lithium nucleation on Au(111) did not follow any of the applied nucleation mechanisms neither and the in situ STM images showed that the lithium UPD process occurs via layer-by-layer with the formation of three monolayers.
STUDY OF THE ELECTRODEPOSITIONS OF LITHIUM AND GALLIUM ON Au(111) AND HOPG USING IONIC LIQUIDS AS ELECTROLYTES
Keywords: Físico-química; Eletroquímica; Eletrodos; CIENCIAS EXATAS E DA TERRA::QUIMICA